Mass Hysteria – Narratives and Impact (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Countless episodes of mass hysteria have occurred throughout history in different time frames and across different cultures. Mass hysteria is an exceptional psychological phenomenon in which large groups of people began to feel the same symptoms as felt by the index case and show irrational behaviour. It has no plausible pathological cause but can be influenced by factors such as fear, anxiety, stress etc.This paper is written with an objective to examine the phenomenon of collective hysteria in the Indian context. It revisits the cases of mass hysteria that occurred in India, particularly Delhi from the start of the 21st century to 2017 and examines the role of cultural factors and media in influencing the outcome of mass hysteria. It interprets how the narratives of the masses and authorities on mass hysteria impact the day – to day lives of the people.